2009
DOI: 10.1063/1.3153116
|View full text |Cite
|
Sign up to set email alerts
|

Doping selective lateral electrochemical etching of GaN for chemical lift-off

Abstract: An electrochemical etching based on oxalic acid was developed for use in the chemical lift-off of GaN epitaxial structures. It was shown that only the Si-doped n-GaN layer was etched away, while the p-type and undoped GaN layers were not etched at all. The etch rate and the remaining structure were analyzed for various doping concentrations and etching voltages. A lateral etch rate of 12 μm/min was achieved under 60 V for n-type doping concentration of 8×1018 cm−3. This doping selective etching was used to lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 10 publications
0
74
0
Order By: Relevance
“…This non-uniformity of the carrier concentration is believed to be dependent on the growth direction (i.e., the growth rate); it being reported by Park. et al [23] that electrochemical etching in the dark can remove highly-doped n + -GaN, whereas unintentionally-doped n-GaN showed complete resistance to etching without UV illumination. Tseng et al [19] suggested that etching in the dark involves tunneling between the semiconductor/electrolyte interface, which is inhibited by the larger depletion layer in unintentionally doped n-GaN.…”
Section: Morphology Of the Etched Gan Surfacementioning
confidence: 98%
“…This non-uniformity of the carrier concentration is believed to be dependent on the growth direction (i.e., the growth rate); it being reported by Park. et al [23] that electrochemical etching in the dark can remove highly-doped n + -GaN, whereas unintentionally-doped n-GaN showed complete resistance to etching without UV illumination. Tseng et al [19] suggested that etching in the dark involves tunneling between the semiconductor/electrolyte interface, which is inhibited by the larger depletion layer in unintentionally doped n-GaN.…”
Section: Morphology Of the Etched Gan Surfacementioning
confidence: 98%
“…Recently, a wet chemical etching method, which can provide the advantages of low damage, low cost, and wide range of selectivity in different crystal orientations, has been applied to selective etching between GaN and c-plane sapphire [8]. In a previous report, although the possibility of chemical lift-off was shown, separating the GaN layer from the sapphire substrate was difficult due to the slow etching rate of the wet chemical method [9].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Nakamura et al reported highpower (30 mW) and high-efficiency blue InGaN/GaN light-emitting diodes on a free-standing (10-1-1) GaN substrate [6]. Owing to the apparent advantages of using a free-standing GaN substrate, many groups have studied the fabrication of free-standing GaN substrates using various methods [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, suspended p -GaN membranes are produced that rest against pillars formed in regions under the mask. [45]. Holes are generated via Zener breakdown in this process by applying a high reverse bias voltage (∼60 V) to the highly doped layer.…”
Section: Fabrication Of Gan Membranes By Wet Etching Undercuttingmentioning
confidence: 99%